Could erectile dysfunction be a marker of atherosclerotic cardiovascular disease? - G. G. Sharvadze; M. N. Mamedov; E. A. Poddubskaya; D. G. Kurbatov (Кардиоваскулярная терапия и профилактика, 1970)
The paper is focused on erectile dysfunction (ED) as an inter-disciplinary problem. The detailed analysis of relevant clinical trials and meta-analyses is performed, demonstrating a causal relationship between ED and coronary heart disease, arterial hypertension, dyslipidemias, and diabetes mellitus. The role of common cardiovascular (CVD) risk factors (RFs) in ED development, as well as a shared, endothelial dysfunction-related pathogenetic mechanism of CVD, is discussed. The prevalence of ED and androgen deficiency, together with their link to metabolic syndrome (MS), is presented. It is shown that ED could be regarded as CVD predictor, and that early diagnostics of the RFs common for CVD and ED can be used for risk prediction and identification of highrisk groups. Since metabolic RFs are common for CVD, ED, and androgen deficiency, further research in this area may facilitate more efficient approaches to prevention and treatment of these diseases.